Supercapillary Architecture‐Activated Two‐Phase Boundary Layer Structures for Highly Stable and Efficient Flow Boiling Heat Transfer. Issue 2 (11th November 2019) - Li, Wenming; Wang, Zuankai; Yang, Fanghao; Alam, Tamanna; Jiang, Mengnan; Qu, Xiaopeng; Kong, Fengyu; Khan, Ahmed Shehab; Liu, Minjie; Alwazzan, Mohammad; Tong, Yan; Li, Chen
Abstract: Development of smaller, faster, and more powerful electronic devices requires effective cooling strategies to efficiently remove ever‐greater heat. Phase‐change heat transfer such as boiling and evaporation has been widely exploited in various water‐energy industries owing to its efficient heat transfer mode. Despite extensive progress, it remains challenging to achieve the physical limit of flow boiling due to highly transitional and chaotic nature of multiphase flows as well as unfavorable boundary layer structures. Herein, a new strategy that promises to approach the physical limit of flow boiling heat transfer is reported. The flow boiling device with multiple channels is characterized with the design of micropinfin fences, which fundamentally transforms the boundary layer structures and imparts significantly higher heat transfer coefficient even at high heat flux conditions, in which boiling heat transfer is usually deteriorated due to the development of dryout starting from outlet regions and severe two‐phase flow instabilities. Moreover, the approaching of physical limit is achieved without elevating pressure drop. Abstract : Inspired by natural surfaces to trap thin liquid films, textured supercapillary structures are designed in a microfluidic device to fundamentally transform the conventional chaotic phase‐transition process into a desirable two‐phase boundary layer structure. Exceptional two‐phase and thermal transport are achieved, approaching the physical limit of flow boiling heat transfer.